High-performance additive and steel slag doped cementing material applied to high-performance additive

Through the combination of calcium citrate, modified sodium alginate and modified diatomaceous earth, the problem of steel slag decreases and cracks in gelled materials is solved, the application of high-performance admixtures is realized, and the comprehensive performance of gelled materials is improved.

CN120518346APending Publication Date: 2025-08-22NANJING TENGHENG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510714674.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

When used in gelling materials, steel slag has problems such as large fluctuations in composition, low activity, poor volume stability, resulting in decreased strength and cracking. The single function of existing admixtures cannot effectively solve these problems.

Method used

A specific proportion of calcium citrate, modified sodium alginate and modified diatomaceous earth are used to form a high-performance admixture, which enhances the mechanical strength of the gelled material by improving the hydration properties and interface properties of the steel slag.

Benefits of technology

It significantly improves the late strength and durability of steel slag gelling materials, is suitable for high-volume steel slag systems, and improves the hydration and interface performance of steel slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-performance additive and a steel-slag-doped cementing material applied to the high-performance additive, and relates to the technical field of cementing materials. The high-performance additive is prepared from the following components in parts by weight: 0.5 to 1 part of calcium citrate, 1.5 to 2 parts of modified sodium alginate, 4 to 6 parts of modified diatomite and 0.01 to 0.03 part of potassium persulfate. The modified sodium alginate is prepared from the following raw materials: oxidized sodium alginate, 4-hydroxycinnamamide, aminated graphene and sodium sulfanilate. The raw materials of the modified diatomite comprise alkali lignin and aminated diatomite. The invention provides the high-performance additive which is applied to the binding material doped with the steel slag, so that the problems of low activity of the steel slag and single function of the traditional additive are solved, the comprehensive improvement of the performance of the binding material is also realized, and the binding material has environmental protection property and economic benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementitious materials, in particular to a high-performance admixture and a cementitious material doped with steel slag using the same. Background Art

[0002] With the rapid development of the construction industry, the performance requirements for cementitious materials are increasing. Traditional Portland cement production is energy-intensive and relies on non-renewable resources such as limestone. Furthermore, the steel industry produces a large amount of steel slag annually, with a comprehensive utilization rate of less than 30%, resulting in large-scale stockpiling, land occupation, and environmental pollution. Therefore, incorporating steel slag into cementitious materials can both increase the utilization rate of steel slag waste and improve the resource dependence of the construction industry.

[0003] Currently, the application of steel slag in cementitious materials faces the following difficulties due to its large compositional fluctuations, low activity, and poor volume stability: Steel slag contains minerals with a high calcium-to-silicon ratio, which leads to slow hydration; free oxides delay hydration and easily cause expansion; and the porous interface between the steel slag and the matrix leads to strength loss and cracking during application, limiting its large-scale application. External additives can improve these deficiencies, but most commercially available additives have a single function. For example, alkaline activators improve early strength but increase the risk of cracking; sulfate activators, on the other hand, are ineffective against the iron phase in steel slag, have poor adaptability to the slag, and exhibit low overall performance.

[0004] In summary, solving the above problems, preparing a high-performance admixture, and applying it to cementitious materials doped with steel slag have important application value. Summary of the Invention

[0005] The object of the present invention is to provide a high-performance admixture and a slag-doped cementitious material using the same, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A high-performance admixture comprises the following components: by weight, 0.5 to 1 parts of calcium citrate, 1.5 to 2 parts of modified sodium alginate, and 4 to 6 parts of modified diatomaceous earth.

[0008] More optimally, the raw materials of the modified sodium alginate include oxidized sodium alginate, 4-hydroxycinnamic acid amide, amino graphene, and sodium p-aminobenzenesulfonate in a mass ratio of 5: (0.2-0.3): (1-1.5): (0.2-0.3).

[0009] More optimally, the preparation of the modified sodium alginate comprises the following steps:

[0010] S1.1: Add graphene oxide and aminosilane coupling agent to ethanol aqueous solution in sequence, stir at 60-70°C for 4-6 hours, wash, and dry to obtain amino-treated graphene;

[0011] S1.2: Sodium alginate is added to deionized water, followed by an aqueous sodium periodate solution. The mixture is reacted at room temperature in the dark for 3-5 hours. Ethylene glycol is added to terminate the reaction, followed by dialysis and drying to obtain oxidized sodium alginate.

[0012] S1.3: Add oxidized sodium alginate to deionized water, and add an aqueous dispersion containing 4-hydroxycinnamic acid amide, amino-modified graphene, and sodium p-aminobenzenesulfonate; stir at 45-55° C. for 4-5 hours, wash, and dry to obtain modified sodium alginate.

[0013] More optimally, in the raw material of the aminated graphene, the mass ratio of graphene oxide to aminosilane coupling agent is 1:0.5~0.8; in the raw material of the sodium alginate oxide, the mass ratio of sodium alginate to sodium periodate aqueous solution is 0.5:5~5.5; wherein the concentration of the sodium periodate aqueous solution is 8~10wt%.

[0014] More optimally, the raw materials of the modified diatomaceous earth include alkali lignin and amino diatomaceous earth in a mass ratio of 1:1.

[0015] More optimally, the preparation of the modified diatomaceous earth includes the following steps:

[0016] S2.1: Add diatomaceous earth and aminosilane coupling agent in a mass ratio of 1:0.2-0.5 to an ethanol aqueous solution, stir at 60-70°C for 4-6 hours, wash, and dry to obtain amino diatomaceous earth;

[0017] S2.2: Alkali lignin and amino-modified diatomaceous earth are sequentially added to deionized water and dispersed evenly. Glutaraldehyde is added, and the mixture is stirred at 65-70° C. for 4-6 hours. The mixture is washed and dried to obtain modified diatomaceous earth.

[0018] A cementitious material doped with steel slag and using a high-performance admixture, the cementitious material comprising the following components: by weight, 24-36 parts of steel slag, 6-9 parts of a high-performance admixture, 4-7 parts of lime, 3-5 parts of gypsum, 0.5-0.8 parts of sodium hydroxide, 0.35-0.58 parts of sodium silicate, and 0.01-0.03 parts of potassium persulfate.

[0019] More optimally, when the cementitious material is used, the water-cement ratio is 0.45~0.55.

[0020] Compared with the prior art, the beneficial effect achieved by the present invention is that the admixture is formed by compounding calcium citrate, modified sodium alginate and modified diatomaceous earth in a specific proportion, which effectively improves the hydration and interfacial properties of steel slag, thereby effectively improving the comprehensive properties such as the mechanical strength of the gel material containing doped steel slag.

[0021] Sodium alginate, a natural polysaccharide, forms a gel network in alkaline environments, effectively improving the fluidity and water retention of cementitious materials and reducing the sedimentation and delamination of steel slag. Its carboxyl groups allow it to crosslink with metal ions in the slag, forming a three-dimensional structure and enhancing early strength. Furthermore, the proposed method further modifies the alginate by first oxidizing it and then grafting it with 4-hydroxycinnamamide, amino-graphene, and sodium p-aminobenzenesulfonate. This promotes the formation of a denser CSH gel, effectively enhancing its overall strength. Firstly, because 4-hydroxycinnamamide contains phenolic hydroxyl groups, it can also coordinate with metal ions in the slag and optimize the distribution of hydration products, thereby improving later-stage strength. Furthermore, its benzene rings improve the polymer network of the sodium alginate, further enhancing strength. Secondly, the amino-graphene oxide, due to its nano-reinforcement effect, can fill micropores, improve the porous interface between the slag and the matrix, and enhance interfacial bonding. Furthermore, it can regulate hydration, promote uniform nucleation of the CSH gel, and improve later-stage strength. Its dispersibility is also due to the grafting with sodium alginate, which effectively avoids agglomeration. Thirdly, the sulfonic acid group in sodium p-aminobenzenesulfonate can promote hydration uniformity and promote early hydration nucleation.

[0022] Diatomaceous earth, with its microaggregate effect, can effectively fill macropores, refine the pore structure, and enhance density. Its porous structure absorbs water, releasing active substances that react with steel slag to produce secondary hydration (a pozzolanic reaction), forming a CSH gel and improving later-stage strength. In this scheme, it is combined with alkali lignin to form modified diatomaceous earth. Alkali lignin can be loaded onto the surface of steel slag. During hydration, it promotes slag activity and nucleation, forming a dense gel structure while inhibiting the expansion of free oxides. Alkali lignin also forms stable complexes with metal ions in the steel slag, strengthening the organic-inorganic interface. At the same time, alkali lignin can form a synergistic effect with sodium alginate: alkali lignin disperses particles, and sodium alginate forms a gel skeleton, jointly improving the fluidity of the slurry and the density after hardening; alkali lignin slows down the setting through adsorption, and sodium alginate slows down the setting through Ca²⁺ consumption, synergistically extending the hydration time and optimizing the microstructure; the Ca²⁺ responsiveness of sodium alginate re-gels at the cracks, synergistically inhibiting crack propagation with alkali lignin.

[0023] Calcium citrate is a common admixture. In this solution, calcium citrate preferentially chelates Ca²⁺ to delay early hydration, while sodium alginate subsequently forms a gel network with the remaining Ca²⁺, resulting in a dual-stage control mechanism of "retarded setting and structural enhancement." Calcium citrate also allows diatomaceous earth to exert its pozzolanic effect for a longer period of time, generating more CSH gel and improving the slag-cement interface.

[0024] In summary, the combined use of the three can achieve the synergy of "retarding-gel-filling", significantly improving the later strength and durability of steel slag cementitious materials, making them suitable for high-content steel slag systems. DETAILED DESCRIPTION

[0025] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0026] It should be noted that the following parts are by weight, and all raw materials involved in the present invention are purchased from manufacturers without any special restrictions. Examples include: In the following examples, sodium alginate has a purity of 99% and is produced by Mingyue; calcium citrate has a purity of 99% and is produced by Nanjing Songguan; diatomaceous earth has a moisture content of ≤0.3% and is produced by Zhanteng; alkali lignin is 471003 and is produced by SIGMA; 4-hydroxycinnamic acid has a CAS number of 194940-15-3; sodium p-aminobenzenesulfonate has a CAS number of 15898-43-8; steel slag includes calcium oxide, silicon dioxide, iron oxide, aluminum oxide, magnesium oxide, and other amorphous minerals; lime is quicklime produced by Yandong Mining; and gypsum is desulfurized gypsum produced by Zhenxing.

[0027] Example 1: A method for preparing a cementitious material doped with steel slag using a high-performance admixture, comprising the following steps:

[0028] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0029] (2) Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to 90 wt% ethanol aqueous solution, stir at 60 ° C for 4 hours, wash and dry to obtain amino diatomite; S2.2: Add 1 part of alkali lignin and 1 part of amino diatomite to 10 parts of deionized water in sequence and disperse evenly, add 0.2 parts of glutaraldehyde, stir at 65 ° C for 5 hours, wash and dry to obtain modified diatomite;

[0030] Step 2: Compounding 0.8 parts of calcium citrate, 1.7 parts of modified sodium alginate, and 5.5 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0031] Step 3: 32 parts of steel slag, 8 parts of high-performance admixture, 6 parts of lime, 4 parts of gypsum, 0.5 parts of sodium hydroxide, 0.48 parts of sodium silicate, and 0.02 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0032] Example 2: A method for preparing a cementitious material doped with steel slag using a high-performance admixture, comprising the following steps:

[0033] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0034] (2) Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to 90 wt% ethanol aqueous solution, stir at 60 ° C for 4 hours, wash and dry to obtain amino diatomite; S2.2: Add 1 part of alkali lignin and 1 part of amino diatomite to 10 parts of deionized water in sequence and disperse evenly, add 0.2 parts of glutaraldehyde, stir at 65 ° C for 5 hours, wash and dry to obtain modified diatomite;

[0035] Step 2: Compound 0.5 parts of calcium citrate, 1.5 parts of modified sodium alginate, and 4 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0036] Step 3: 24 parts of steel slag, 6 parts of high-performance admixture, 4 parts of lime, 3 parts of gypsum, 0.5 parts of sodium hydroxide, 0.35 parts of sodium silicate, and 0.01 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0037] Example 3: A method for preparing a cementitious material doped with steel slag using a high-performance admixture, comprising the following steps:

[0038] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0039] (2) Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to 90 wt% ethanol aqueous solution, stir at 60 ° C for 4 hours, wash and dry to obtain amino diatomite; S2.2: Add 1 part of alkali lignin and 1 part of amino diatomite to 10 parts of deionized water in sequence and disperse evenly, add 0.2 parts of glutaraldehyde, stir at 65 ° C for 5 hours, wash and dry to obtain modified diatomite;

[0040] Step 2: Compound 1 part of calcium citrate, 2 parts of modified sodium alginate, and 6 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0041] Step 3: 36 parts of steel slag, 9 parts of high-performance admixture, 7 parts of lime, 5 parts of gypsum, 0.8 parts of sodium hydroxide, 0.58 parts of sodium silicate, and 0.03 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0042] Comparative Example 1: Sodium alginate was used directly; the rest was the same as Example 1; specifically, the following steps were included:

[0043] Step 1: Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to a 90 wt% ethanol aqueous solution, stir at 60°C for 4 hours, wash, and dry to obtain amino-modified diatomite. S2.2: Add 1 part alkali lignin and 1 part amino-modified diatomite to 10 parts deionized water, disperse uniformly, add 0.2 part glutaraldehyde, stir at 65°C for 5 hours, wash, and dry to obtain modified diatomite.

[0044] Step 2: Compound 0.8 parts of calcium citrate, 1.7 parts of sodium alginate, and 5.5 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0045] Step 3: 32 parts of steel slag, 8 parts of high-performance admixture, 6 parts of lime, 4 parts of gypsum, 0.5 parts of sodium hydroxide, 0.48 parts of sodium silicate, and 0.02 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0046] Comparative Example 2: Directly using amino diatomaceous earth; the rest is the same as Example 1; specifically comprising the following steps:

[0047] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0048] (2) Preparation of amino diatomite: diatomite and aminosilane coupling agent KH792 were added to a 90 wt% ethanol aqueous solution in a mass ratio of 1:0.2, stirred at 60 °C for 4 hours, washed and dried to obtain amino diatomite;

[0049] Step 2: Compound 0.8 parts of calcium citrate, 1.7 parts of modified sodium alginate, and 5.5 parts of amino diatomaceous earth to obtain a high-performance admixture;

[0050] Step 3: 32 parts of steel slag, 8 parts of high-performance admixture, 6 parts of lime, 4 parts of gypsum, 0.5 parts of sodium hydroxide, 0.48 parts of sodium silicate, and 0.02 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0051] Comparative Example 3: Calcium citrate was not introduced, and the rest was the same as Example 1; specifically, the following steps were included:

[0052] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0053] (2) Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to 90 wt% ethanol aqueous solution, stir at 60 ° C for 4 hours, wash and dry to obtain amino diatomite; S2.2: Add 1 part of alkali lignin and 1 part of amino diatomite to 10 parts of deionized water in sequence and disperse evenly, add 0.2 parts of glutaraldehyde, stir at 65 ° C for 5 hours, wash and dry to obtain modified diatomite;

[0054] Step 2: Compounding 1.7 parts of modified sodium alginate and 5.5 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0055] Step 3: 32 parts of steel slag, 7.2 parts of high-performance admixture, 6 parts of lime, 4 parts of gypsum, 0.5 parts of sodium hydroxide, 0.48 parts of sodium silicate, and 0.02 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0056] Comparative Example 4: Increasing the amount of modified sodium alginate introduced, and the rest is the same as Example 1; specifically comprising the following steps:

[0057] Step 1: (1) Preparation of modified sodium alginate: S1.1: Graphene oxide and aminosilane coupling agent KH792 in a mass ratio of 1:0.6 are added to 80 wt% ethanol aqueous solution in sequence, stirred at 60 ° C for 5 hours, washed and dried to obtain amino graphene; S1.2: 0.5 parts of sodium alginate are added to 10 parts of deionized water, 5.2 parts of 10 wt% sodium periodate aqueous solution are added, and the reaction is carried out at room temperature in the dark for 4 hours, ethylene glycol is added to terminate the reaction, dialyzed and dried to obtain oxidized sodium alginate; S1.3: 5 parts of oxidized sodium alginate are added to 20 parts of deionized water, and an aqueous dispersion containing 0.2 parts of 4-hydroxycinnamic acid, 1 part of amino graphene and 0.3 parts of sodium p-aminobenzenesulfonate is added; stirred at 50 ° C for 4 hours, washed and dried to obtain modified sodium alginate;

[0058] (2) Preparation of modified diatomite: S2.1: Add diatomite and aminosilane coupling agent KH792 in a mass ratio of 1:0.2 to 90 wt% ethanol aqueous solution, stir at 60 ° C for 4 hours, wash and dry to obtain amino diatomite; S2.2: Add 1 part of alkali lignin and 1 part of amino diatomite to 10 parts of deionized water in sequence and disperse evenly, add 0.2 parts of glutaraldehyde, stir at 65 ° C for 5 hours, wash and dry to obtain modified diatomite;

[0059] Step 2: Compounding 0.8 parts of calcium citrate, 2.7 parts of modified sodium alginate, and 5.5 parts of modified diatomaceous earth to obtain a high-performance admixture;

[0060] Step 3: 32 parts of steel slag, 9 parts of high-performance admixture, 6 parts of lime, 4 parts of gypsum, 0.5 parts of sodium hydroxide, 0.48 parts of sodium silicate, and 0.02 parts of potassium persulfate were mixed and ground for 60 minutes to obtain a cementitious material doped with steel slag.

[0061] Performance Test 1: The slag-doped cementitious material prepared in Example 1 was tested for mortar according to the requirements of GB / T2419-2005, "Determination of fluidity of cement mortar." The setting time of the cementitious material was tested according to the requirements of GB / T1346-2011, "Test methods for water consumption, setting time, and soundness of cement of standard consistency."

[0062] Conclusion: The prepared cementitious material has a fluidity of 198, an initial setting time of 224 minutes, and a final setting time of 385 minutes; it has good performance.

[0063] Performance Test 2: The strength of the slag-doped cementitious materials prepared in the Examples and Comparative Examples was tested. The materials were prepared according to the relevant requirements of GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)" with a water-cement ratio of 0.5. The 3d and 28d strengths of the mortar specimens were tested. The resulting properties are shown in the following table:

[0064]

[0065] Conclusion: The admixture prepared in this application is used in a cementitious material based on steel slag. In practical applications, it improves the defects of steel slag and effectively improves the strength, especially the late strength. In Comparative Example 1, the direct use of sodium alginate reduces the hydration property, resulting in a decrease in strength. In Comparative Example 2, the amino-treated diatomaceous earth and the lack of alkali lignin lead to a decrease in related properties. In Comparative Example 3, the lack of calcium citrate leads to an increase in local defects and a decrease in synergistic effects, resulting in a decrease in strength. In Comparative Example 4, the increased amount of modified sodium alginate introduced leads to an excessive delay in gelation, a decrease in the continuity of the hydration product, and a decrease in early strength.

[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

Claims

1. A high-performance admixture, characterized in that: The high-performance admixture comprises the following components: by weight, 0.5 to 1 parts of calcium citrate, 1.5 to 2 parts of modified sodium alginate, and 4 to 6 parts of modified diatomaceous earth.

2. A high performance admixture according to claim 1, characterized in that: The raw materials of the modified sodium alginate include oxidized sodium alginate, 4-hydroxycinnamic acid amide, amino graphene, and sodium p-aminobenzenesulfonate in a mass ratio of 5: (0.2-0.3): (1-1.5): (0.2-0.3).

3. A high performance admixture according to claim 2, characterized in that: The preparation of the modified sodium alginate comprises the following steps: S1.1: Add graphene oxide and aminosilane coupling agent to ethanol aqueous solution in sequence, stir at 60-70°C for 4-6 hours, wash, and dry to obtain amino-treated graphene; S1.2: Sodium alginate is added to deionized water, followed by an aqueous sodium periodate solution. The mixture is reacted at room temperature in the dark for 3-5 hours. Ethylene glycol is added to terminate the reaction, followed by dialysis and drying to obtain oxidized sodium alginate. S1.3: Add oxidized sodium alginate to deionized water, and add an aqueous dispersion containing 4-hydroxycinnamic acid amide, amino-modified graphene, and sodium p-aminobenzenesulfonate; stir at 45-55° C. for 4-5 hours, wash, and dry to obtain modified sodium alginate.

4. A high performance admixture according to claim 3, characterized in that: In the raw materials of the aminated graphene, the mass ratio of graphene oxide to aminosilane coupling agent is 1:0.5-0.8; in the raw materials of the oxidized sodium alginate, the mass ratio of sodium alginate to sodium periodate aqueous solution is 0.5:5-5.5; wherein the concentration of the sodium periodate aqueous solution is 8-10wt%.

5. A high performance admixture according to claim 1, characterized in that: The raw materials of the modified diatomaceous earth include alkali lignin and amino diatomaceous earth in a mass ratio of 1:

1.

6. A high performance admixture according to claim 5, characterized in that: The preparation of the modified diatomaceous earth comprises the following steps: S2.1: Add diatomaceous earth and aminosilane coupling agent in a mass ratio of 1:0.2-0.5 to an ethanol aqueous solution, stir at 60-70°C for 4-6 hours, wash, and dry to obtain amino diatomaceous earth; S2.2: Alkali lignin and amino-modified diatomaceous earth are sequentially added to deionized water and dispersed evenly. Glutaraldehyde is added, and the mixture is stirred at 65-70° C. for 4-6 hours. The mixture is washed and dried to obtain modified diatomaceous earth.

7. A cementitious material doped with steel slag using a high-performance admixture, characterized by: The cementitious material comprises the high performance admixture according to claim 1.

8. The high-performance admixture-doped steel slag cementitious material according to claim 7, characterized in that: The cementitious material comprises the following components: by weight, 24 to 36 parts of steel slag, 6 to 9 parts of high-performance admixture, 4 to 7 parts of lime, 3 to 5 parts of gypsum, 0.5 to 0.8 parts of sodium hydroxide, 0.35 to 0.58 parts of sodium silicate, and 0.01 to 0.03 parts of potassium persulfate.

9. The high-performance admixture-doped steel slag cementitious material according to claim 8, characterized in that: When the cementitious material is used, the water-to-cement ratio is 0.45-0.55.

Citation Information

Patent Citations

  • Additive for muck solidification and preparation method thereof

    CN117923843A

  • Steel slag-based composite cementing material as well as preparation method and application thereof

    CN119591338A

Cited By

  • Reactive powder concrete doped with steel slag and preparation process

    CN121573943A